1993
DOI: 10.1007/bf01965482
|View full text |Cite
|
Sign up to set email alerts
|

Comparative differences in Ontario farmers' environmental attitudes

Abstract: This paper provides an analysis of a 1991 survey of the views of a stratified random sample of 1,105 Ontario farmers. Factor analysis, Kruskal--Wallis one-way ANOVA, chi-square and correlations were used to identify differences in farmers' attitudes toward rural environmental issues as a function of their demographic and farm characteristics. Younger, well-educated farmers, especially if female, were most concerned about the seriousness of rural environmental degradation. The largest operators expressed the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 8 publications
1
14
0
1
Order By: Relevance
“…Earlier work (Filson, 1993) showed that the biggest Ontario commercial farmers were most likely to oppose environmental regulations and restrictions on the use of chemicals. These commercial farmers were also the group most opposed to meas-ures geared to farmer equalization.…”
Section: The Problemmentioning
confidence: 98%
See 1 more Smart Citation
“…Earlier work (Filson, 1993) showed that the biggest Ontario commercial farmers were most likely to oppose environmental regulations and restrictions on the use of chemicals. These commercial farmers were also the group most opposed to meas-ures geared to farmer equalization.…”
Section: The Problemmentioning
confidence: 98%
“…The final province-wide question-naire was formulated from information and questions derived from the earlier surveys, a quality of life survey developed by McCoy (1992) and a questionnaire designed and pretested in Australia by Black and Reeve (1992). Comparisons were made with 2,044 Australian farmers on rural environmental issues (see Filson, 1993). A similar comparative analysis in relation to Russian farmers is in progress, showing, for instance, that even "privatized" Moscow Region farmers usually expect their government to play a much greater role in establishing the conditions for sustainable agriculture than do Ontario farmers (Filson et al, forthcoming).…”
Section: Survey Proceduresmentioning
confidence: 99%
“…Filson, 1993;Bager & Proost, 1997;Bonnieux et al, 1998;Elis et al, 1999;Vanslembrouck et al, 2002;Mathijs, 2003;Brodt et al, 2006;Siebert et al, 2006;van Rensburg et al, 2009;Boon et al, 2010;Murphy et al, 2011). However, reviews of the literature observe age to be an unreliable indicator (Rougoor et al 1998;Pannell et al, 2006;Knowler & Bradshaw, 2007).…”
Section: Age Of the Owner Occupier/managermentioning
confidence: 99%
“…Consequently, it is widely believed that the higher the level of formal education the more likely the farmer will be to engage with environmental programs and approaches to agriculture. There are numerous studies suggesting that education enhances, for example, the adoption of or attitudes to Barreiro-Hurlé et al, 2010), farmers' environmental attitudes (Filson, 1993) and investment in sustainability measures (Jay, 2005). However, many studies have also found no relationship ).…”
Section: Formal Educationmentioning
confidence: 99%
“…Alternative models, such as the transactional model of behaviour, propose that attitudes can also influence behaviour directly, and that these attitudes are affected by psychological and environmental variables (Bentler and Speckart, 1979;Lazarus and Folkman, 1984). These theories have been applied to the economic behaviour of a range of natural resource-users, and results suggest that personal and business characteristics significantly affect the attitudes and economic behaviours of farmers and fishers (Featherstone and Goodwin, 1993;Filson, 1993;Traoré et al, 1998;Willock et al, 1999a,b;Austin et al, 2001;Jacobson et al, 2003). Specific studies on fishers indicate that their behaviour can be influenced by a combination of factors, including their attitudes (for example, regarding the legitimacy of the regulatory process), a social component (including moral values and peer pressure) and various demographic variables (Jentoft and Davis, 1993;Hart, 1998;Hatcher et al, 2000;Blyth et al, 2002;Eggert and Ellegård, 2003;Flaaten and Heen, 2005;Richardson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%